Radiation shielding parameters and Micro-Raman spectral analysis of some pyroclastic rocks - Yilmaz, Demet; Kilic, Ayse Didem; Kalecik, Sedanur (Pergamon-Elsevier Science Ltd, 2023)
In this study, the radiation shielding parameters of some pyroclastic rocks (Karabakir, Elazig) were experimentally measured at 59.54-661.62 keV energy region. In addition, theoretical mass attenuation coefficients were calculated. Fast neutron removal cross section, exposure buildup factor, mass stopping power and projected range values for proton (H1) and alpha (He+2) particles were theoretically determined. The equivalent dose rates due to fast neutrons absorption by rock samples was measured experimentally using a241Am-Be fast neutron source with 10 mCi activity. Also, the elemental analysis of pyroclastic rocks was done by instrumental neutron activation analysis and inductively coupled plasma mass spectrometry. Minerals type and rock strength were evaluated by micro-Raman spectroscopy methods. The dose rate at detector is D0 when there is no sample between the neutron source and the detector, the dose rate at detector is Dd when there is a K-8 rock sample. The difference between the dose rates (Ds), was calculated and the equivalent dose rate absorbed by the K-8 rock sample was obtained as 0.2667 mu Sv forward slash h. It is observed that K-8 rocks sample is a promising choice for gamma, neutron, proton and alpha shielding.
Keywords: Pyroclastic rock; Gamma shielding; Neutron shielding; Instrumental neutron activation analysis; Raman spectroscopy